2018
DOI: 10.3390/jcm7100305
|View full text |Cite
|
Sign up to set email alerts
|

Serum Urokinase-Type Plasminogen Activator Receptor Does Not Outperform C-Reactive Protein and Procalcitonin as an Early Marker of Severity of Acute Pancreatitis

Abstract: Severe acute pancreatitis (SAP) concerns 10–20% of acute pancreatitis (AP) patients and is associated with a poor prognosis and high mortality. An early prognosis of the unfavorable outcome, transfer to an intensive care unit (ICU) and the introduction of an adequate treatment are crucial for patients’ survival. Recently, the elevated circulating urokinase-type plasminogen activator receptor (uPAR) has been reported to predict SAP with a high diagnostic accuracy among patients in a tertiary center. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 37 publications
2
48
0
1
Order By: Relevance
“…In our study acute pancreatitis was more commonly seen in men associated with alcoholism, followed by gall stones in females, similar to a study conducted at IPGMER, Kolkata Eastern India from January 2014 to January 2017 in 234 patients. 26 Procalcitonin in our study was found to be high in patients of severe acute pancreatitis and the same observation were made at two different study done at Poland by Kolber et al 27 and at Finland by Back et al 28 receptively.…”
Section: R E S U L T Ssupporting
confidence: 88%
“…In our study acute pancreatitis was more commonly seen in men associated with alcoholism, followed by gall stones in females, similar to a study conducted at IPGMER, Kolkata Eastern India from January 2014 to January 2017 in 234 patients. 26 Procalcitonin in our study was found to be high in patients of severe acute pancreatitis and the same observation were made at two different study done at Poland by Kolber et al 27 and at Finland by Back et al 28 receptively.…”
Section: R E S U L T Ssupporting
confidence: 88%
“…At present, no single laboratory marker can be recommended for the early prediction of the development of OF in AP. Recent studies showed that angiopoietin-2(a marker of vascular leak syndrome) [30] or serum urokinase-type plasminogen activator receptor (uPAR) [31] can be applied as a marker in predicting persistent organ failure. Unfortunately, the detections of these indicators are not widely used so far and is difficult to obtain in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that angiopoietin-2(a marker of vascular leak syndrome) [30] or serum urokinase-type plasminogen activator receptor (uPAR) [31] can be applied as a marker in predicting persistent organ failure. Unfortunately, the detections of these indicators are not widely used so far and is difficult to obtain in clinical practice.…”
Section: Discussionmentioning
confidence: 99%